Composition and Diversity of Forestry Plant Species in Forest Areas Manado State University, North Sulawesi - Fanny Nella Nanlohy; Emma Mauren Moko; Jantje Ngangi; Crescentia M.J Ngangi; Verawati Ida Yani Roring (Postgraduate, University of Mataram, 2024)
Indonesia is an archipelagic country with a tropical climate so it has a large forest area. High rainfall and sufficient solar irradiation make the diversity of living things both flora and fauna very high. This study aims to identify and determine the level of diversity of forestry plants in the forest area of Manado State University, North Sulawesi. This research will be carried out in April - May 2023 in the forest area of Manado State University, North Sulawesi. Sampling in this study was carried out using the Purposive Sampling (Judgmental Sampling) technique with 9 plots in 3 observation stations. The results of the study found that in all sampling plots, there were 17 individuals of forestry plants with 9 species. The highest Important Value Index (IVI) belongs to the species Petrocarpus indicus with an IVI of 61%. The Shannon Winner diversity index H = 2.07 was found to be in the medium category.